The association between domestic violence and contraceptive use Maria MIdea M. Kabamalan. - Orteza, Teodoro Merdegia (Population Institute, College of Social Sciences and Philosophy, University of the Philippines, Diliman, 2019)
The Philippine Statistics Authority (PSA) conducts the National Demographic and Health Survey (NDHS) as primary source of data to assess the demographic and health situation in the country. The women's safety module of the NDHS collects information on more recent experience (in the past 12 months) and the current contraceptive use among married women. This study examines levels, associations, and factors of current use of contraceptive methods, recent experience of domestic violence, and its characteristics. The prevalence of women with current male methods used in contraception was low compared to more than double proportion of women with current female methods used. Results also show that the profile of women with current contraceptive use, by male or female methods, is dependent on woman's individual, marriage, and household characteristics, although women's working status and ownership of the house had slightly lower significance. Currently married women with recent experience of domestic violence are relatively more likely with current use of contraceptives compared with their non-abused peers. The strength of association between recent experience of domestic violence and selected woman's individual, marriage, and household characteristics are significant. In light of these findings, it is recommended that policy makers place emphasis on developing strategies to integrate gender issues that concern women's reproductive health, Although contraception has traditionally been the responsibility of women, men have been involved in decisions about contraception. Men's knowledge of contraception is a key driver of whether men will cooperate and what method they will choose.